The ways of Improving the Innovation Management in Ukraine Using the International Development - Bokovets, Viktoriia; Moskvichova, Olena; Hryhoruk, Iryna; Suprunenko, Svetlana (European Journal of Sustainable Development, 2020)
In the world economic space there is a complex transition from industrial technological system to postindustrial, in which the high tech, informatization and knowledge economy takes on the dominating role of the driving forces of development. Naturally, for such a turn of events, economic science was not well prepared, and today there is a certain gap between the practice of accelerated changes and the scientific provision of these processes. First of all, it concerns the development of a strategy and mechanisms for the development of the country's economy and identifying opportunities for realizing its innovative potential by doing innovative management. The researchers consider innovative management in their work in a number of aspects: science and art of innovative management (I. Dichkivska, P. Zavlin); kind of administrative activity in making decisions on innovations (I. Balabanov, M. Yon, V. Stadnik,); management of innovations (N. Kruglov, A. Porshnev); a system of rules of principles, norms, values orientations that regulate various spheres of innovation activity (V. Vasilenko, L. Oholova). In innovative management, the methods of socio-psychological series, heuristic and collegial (I. Ansoff, B. Gates, L. Karuushkha, A. Morita) prevail. There is a change in the general functions, structure and objectives of management (L. Danilenko, L. Oholova), there are special means and forms of organization of innovation activity (V. Vasilenko, L. Vashchenko).The study of literary sources and their generalization shows the importance of this issue, and requires a more in-depth study and analysis of international experience in implementing innovative measures. The research objective. The main purpose of this study is to analyze measures to stimulate innovation development in the countries of the world, assessment of their effectiveness, as well as consideration of the directions on the basis of their activation of innovation activity in Ukraine. The article reveals the essence of the concept of "innovative management", analyzes the international experience in implementing and stimulating the innovation process. Thus, to summarize, it can be concluded that the experience of leading countries in stimulating innovation usually involves quite similar measures, namely: subsidies, tax cuts or, in some cases, tax holidays, payment of a share of R & D expenditure. The following organizations are created: informational, technical, financial support for business engaged in innovation activities. Stimulates the development of innovations at the level of universities and other scientific institutions. Keywords: innovative management; innovative activity; innovative measures; R&D; innovation.